1995
DOI: 10.1104/pp.108.3.1067
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Photosystem I Polypeptides (Identification of PsaB Domains That May Interact with PsaD)

Abstract: -PsaA and PsaB are homologous integral membrane-proteins that form the heterodimeric core of photosystem I (PSI). We used subunit-deficient PSI complexes from the mutant strains of the cyanobacterium Synechocysfis sp. PCC 6803 t o examine interactions between PsaB and other PSI subunits. lncubation of the wild-type PSI with thermolysin yielded 22-kD C-terminal fragments of PsaB that were resistant t o further proteolysis. Modification of the wildtype PSI with Khydroxysuccinimidobiotin and subsequent cleavage b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Previous work has indicated that a 16-kDa proteolytic fragment detected by anti-PsaB718 in thermolysin-treated ADC4 PS I complex resulted from a cleavage at Leu-531 in the I loop of PsaB (28). Similar proteolytic fragments, such as ChB, ClB, LyA, LyB, ThA in different mutant PS I complexes, were detected.…”
Section: Fig 2 Treatment Of the Subunit-deficient Ps I Complexes Wimentioning
confidence: 55%
See 4 more Smart Citations
“…Previous work has indicated that a 16-kDa proteolytic fragment detected by anti-PsaB718 in thermolysin-treated ADC4 PS I complex resulted from a cleavage at Leu-531 in the I loop of PsaB (28). Similar proteolytic fragments, such as ChB, ClB, LyA, LyB, ThA in different mutant PS I complexes, were detected.…”
Section: Fig 2 Treatment Of the Subunit-deficient Ps I Complexes Wimentioning
confidence: 55%
“…4). Additionally, Xu and Chitnis (28) identified that PsaD may shield the I and K loops of PsaB. When the PS I complexes from the AFK6 and AIC9 strains were treated by proteases, no additional fragments from the N-terminal domains of PsaA and PsaB were observed.…”
Section: Topography Of the Photosystem I Core Proteinsmentioning
confidence: 99%
See 3 more Smart Citations